CORRECTION OF CONTENT OF TOTAL PROTEIN AND UREA IN SERUM OF BLOOD OF NEWBORN CALVES DURING THE FORMATION PERIOD OF COLOSTRAL IMMUNITY - Цвіліховський, М. І.; Голопура, С. І. (Scientific Progress & Innovations, 2014)
Іn this article the results of application of experimental liposomal macrocapsular preparation based on soyabean lecithin for correction of indexes of content of general protein and urea in the serum of blood of newborn calves in the formation period of colostral immunity are provided. It is shown that use of the drug per os newborn calves for 15-20 minutes before feeding them colostrum provides the predominance of catabolic anabolic processes, prevention of occurrence digestive disorders and improves detoxification mechanisms in these animals.